2014
DOI: 10.3386/w19839
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exposure In Utero and Child Academic Achievement

Abstract: We examine the effect of prenatal alcohol exposure on child academic achievement. We use a genetic variant in the maternal alcohol-metabolism gene ADH1B to instrument for alcohol exposure, whilst controlling for the child's genotype on the same variant. We show that the instrument is unrelated to an extensive range of parental characteristics and behaviour. OLS regressions suggest an ambiguous association between alcohol exposure and attainment but there is a strong social gradient in drinking, with mothers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…Other MR studies have similarly contradicted findings from previous observational studies relevant to alcohol use, including outcomes as diverse as cognitive function , children's academic achievement , balance and blood pressure , all finding no protective effect from low‐dose alcohol.…”
mentioning
confidence: 91%
“…Other MR studies have similarly contradicted findings from previous observational studies relevant to alcohol use, including outcomes as diverse as cognitive function , children's academic achievement , balance and blood pressure , all finding no protective effect from low‐dose alcohol.…”
mentioning
confidence: 91%
“…28,29 Studies using different methods, have found drinking at low-moderate levels (between 1-6 units per week) is linked to small decreases in child IQ, educational attainment and behavioural scores compared to not drinking at all during pregnancy. 30,31,32 The strongest evidence is for an increased risk of pre-term birth and low birthweight for mothers that drink more than one unit a week. 33…”
Section: Low Levels Of Drinking During Pregnancymentioning
confidence: 99%
“…For example, the prevalence of alcohol use among pregnant Inuit women in northern Quebec, Canada, was over 6 times higher as compared to that observed in the general population of Canada (60.5% vs 10%, respectively) (Fraser et al, 2012 ). Among women who consumed alcohol in pregnancy in the UK, binge drinking was reported to be more common among women of lower socioeconomic status (SES) (Scholder et al, 2014 ).…”
mentioning
confidence: 99%